HISTORY OF THE EMERGENCE AND DEVELOPMENT OF THE CONCEPTS OF “COMPETENCE” AND “COMPETENCY” - Gulmira Rifovna Tojiboeva; Zilolakhon Umarova (Web of Journals Publishing, 2023)
In this article, it was studied from where and how the concepts of "competence" and "competence" appeared. The criteria for assessing the competence of a teacher are presented, pedagogical experiments are described.
Keywords: competence, competence, pedagogy, education, professional competence.